2012
DOI: 10.1002/chem.201202492
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Magnetic Anisotropy in Heptacoordinate NiII and CoII Complexes

Abstract: The nature and magnitude of the magnetic anisotropy of heptacoordinate mononuclear Ni(II) and Co(II) complexes were investigated by a combination of experiment and ab initio calculations. The zero-field splitting (ZFS) parameters D of [Ni(H(2)DAPBH)(H(2)O)(2)](NO(3))(2)⋅2 H(2)O (1) and [Co(H(2)DAPBH)(H(2)O)(NO(3))](NO(3)) [2; H(2)DAPBH = 2,6-diacetylpyridine bis- (benzoyl hydrazone)] were determined by means of magnetization measurements and high-field high-frequency EPR spectroscopy. The negative D value, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
166
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 148 publications
(184 citation statements)
references
References 28 publications
18
166
0
Order By: Relevance
“…The (117). Adapted with permission from [212], [227], and [226]. Copyright 2013 American Chemical Society.…”
Section: Hepta-coordinated Complexesmentioning
confidence: 98%
See 3 more Smart Citations
“…The (117). Adapted with permission from [212], [227], and [226]. Copyright 2013 American Chemical Society.…”
Section: Hepta-coordinated Complexesmentioning
confidence: 98%
“…Detailed ab initio calculations showed that the high-spin d 7 metal ions with this geometry were expected to have a large and positive D, whereas d 8 metal ions in these coordination environments were predicted to have large and negative D values. It was demonstrated that the main perturbative contributions to D came from the triplet excited states to D and E, but with an essential contribution from the first triplet state [212].…”
Section: Hepta-coordinated Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…A lowering of the symmetry is therefore necessary to observe the property. Molecules with the same symmetry but with different electronic configurations of the magnetic ion (different metal ions or different oxidation states) lead to completely different magnetic anisotropies (easy axis or easy plane and with or without rhombic contribution) so that the ways to improve SMMs are far from being intuitive [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%